Exploring the Work Experiences of School Counselors of Color. Issue 1 (October 2013) - Dollarhide, Colette T.; Bowen, Nikol V.; Baker, Caroline A.; Kassoy, Felice R.; Mayes, Renae D.; Baughman, Amber V.
In spite of research suggesting the importance of diverse professionals in education (Mattison & Aber, 2007), no studies have explored the professional experiences of school counselors of Color. In this exploratory grounded-theory qualitative study, researchers interviewed 19 school counselors of Color. Responses revealed both positive and negative racial experiences in the schools, with mitigating factors involving the school environment. Implications for professional school counselors include advocacy and allyhood.